An Examination of the Prostitution Debate in Action: ‘Unpacking’ the Discourses, Convergences, and Divergences in Bedford - Ruthven, Brittany (Université d'Ottawa / University of Ottawa, 2015)
Prostitution, sex in exchange for consideration, has never been illegal in Canada; however, activities surrounding prostitution have been criminalized in the Criminal Code. These prohibited activities include: working indoors (s. 210 keeping a common bawdy house), providing services to sex workers (s. 212(1)(j) living off of the avails of prostitution), and communicating in public for the purposes of prostitution (s. 213). In 2007 two former and one current sex worker, Terri Jean Bedford, Valerie Scott and Amy Lebovitch challenged the constitutionality of the above laws, arguing that they increased sex workers’ vulnerability to harm. Six years later on June 13th, 2013 the Supreme Court of Canada heard the landmark case Canada (Attorney General) v. Bedford. Prior to hearing the case, the Supreme Court Justices read the submitted factums outlining the arguments of the appellants, respondents, and their interveners. The final decision was released on December 22nd, 2013 and the unanimous decision to strike down all three laws was made. Using a discourse analysis inspired by Michel Foucault, this study ‘unpacks’ the meanings that are constituted within the factums submitted to the Supreme Court regarding the people who engage in sex work and the institution of prostitution. The convergences and divergences within the discourses are presented. Drawing on these findings, while applying the work of Wedeking’s (2010) strategic legal framing alongside the governmentality perspective of risk, the tensions surrounding risk and choice are further explored. In doing so, the relationship between risk (taking/avoiding) and choice (making) is teased out. In this thesis I argue that risk and choice are strategically framed in the submitted factums to demonstrate the (un)constitutionality of Canada’s prostitution laws. Furthermore, I argue that both the appellants and respondents agree that risk avoidance is an acceptable self-governance strategy for sex workers, however they diverge on what they consider to be acceptable risk avoidance measures. The conclusion of this study discusses the decision of Canada (Attorney General) v. Bedford to strike down the three prostitution laws and the subsequent introduction of the Protection of Communities and Exploited Persons Act.
Keywords: Bedford; Prostitution; Sex Work; Prostitutes; Sex Workers; Supreme Court of Canada; Customers; Third parties; Risk; Choice